2012
DOI: 10.1186/1756-0500-5-213
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of grapevine whole-genome gene predictions, functional annotation, categorization and integration of the predicted gene sequences

Abstract: BackgroundThe first draft assembly and gene prediction of the grapevine genome (8X base coverage) was made available to the scientific community in 2007, and functional annotation was developed on this gene prediction. Since then additional Sanger sequences were added to the 8X sequences pool and a new version of the genomic sequence with superior base coverage (12X) was produced.ResultsIn order to more efficiently annotate the function of the genes predicted in the new assembly, it is important to build on as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
198
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(199 citation statements)
references
References 24 publications
1
198
0
Order By: Relevance
“…To report complex alleles consistently, we defined all variants against the 12x grapevine reference genome assembly (Grimplet et al, 2012). There were 2,087,275 single-base differences between Tannat and PN40024, as well as 240,355 (11.5%) ambiguous calls.…”
Section: Genome Sequencing Assembly and Analysis Of Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…To report complex alleles consistently, we defined all variants against the 12x grapevine reference genome assembly (Grimplet et al, 2012). There were 2,087,275 single-base differences between Tannat and PN40024, as well as 240,355 (11.5%) ambiguous calls.…”
Section: Genome Sequencing Assembly and Analysis Of Variantsmentioning
confidence: 99%
“…For genes transferred from the V1 annotation, we integrated the VitisNet annotations (Grimplet et al, 2012). Definitions could be assigned by homology searches to 20,170 of the genes (;58%).…”
Section: Transcriptome Assembly and Identification Of Tannat-specificmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide an overview of their roles, the differentially expressed genes (DEGs) were classified on the basis of a manually improved functional annotation (Grimplet et al, 2012;Supplemental Data Set 2). The significantly overrepresented (P < 0.05) functional categories identified for downregulated and upregulated genes (Supplemental Figure 2 and Supplemental Data Set 2) showed that maturation involves the suppression of diverse metabolic processes, including photosynthesis, energy metabolism, carbohydrate metabolism, cellular component organization, and the cell cycle, which are related to vegetative growth.…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptomes of 35S:MYBC2-L3 and wild-type lines were analyzed using both a coexpression-based approach (Usadel et al, 2009) to identify genes showing negatively correlated profiles with respect to MYBC2-L3 and a twoclass unpaired comparison using significance analysis of microarray (SAM; Table I; Supplemental Data S2). All genes selected by these approaches were automatically annotated against the V1 gene prediction version of the grapevine genome (Grimplet et al, 2012) and manually improved where possible. Among the genes most negatively correlated to MYBC2-L3 expression, we found many structural genes related to phenylpropanoid, general flavonoid, or PA synthesis and transport (Table I; Supplemental Data S2).…”
mentioning
confidence: 99%